Kaolin's characterization and potential in the Boycá department (2007)
In the Colombian oriental mountain range, central region, there is a mining potential for the extraction of white clays, its majority of sedimentary origin, and the deposits are of lacustrine and co-alluvial type. The kaolin locations are known in: Tunja, Siachoque, Tutasá, Gachantivá and Arcabuco municipalities. In the last two there are the most important locations by their extension and for being the mining sites that have benn developed during more than for 50 years into the ceramic production. It is stated a methodology to study the clays in all the development phases of a mining project, beginning with the exploration and accomplishing a higth purity mineral.